THE USING OF VERNACULAR DESIGN TO DEVELOP EDUCATIONAL MEDIA FOR DISASTER MITIGATION THE DIRECTION OF DISASTER MITIGATION STRATEGIES IN THE RING OF FIRE REGION - Rahmatsyam Lakoro; Agus Sachari; Agung EBW; Setiawan Sabana (Proceeding of International Conference on Art, Language, and Culture, 2019)
Indonesia located in the intersection zone of Eurasian Plate, Pacific Ocean Plate and Indo-Australia causing some areas in Indonesia has the potential to experience periodically both earthquakes and tsunami. The education to deal with those circumstances has become a necessity in most parts of Indonesia to build resilience to disaster. This research aims to identify, understand and explain the study of visual content on disaster education media in the strategy of vernacular design. This difference emerges because of the authority of traditional knowledge and the stakeholder of local wisdom which is widely followed by several communities in Indonesian society has different direction in seeing disasters. Educational media that have been developed utilize the spoken culture such as folksongs, folktale or traditional games, but it’s never been evaluated the effectiveness of the media in term of visual communication approach. Technological developments close to the user allow opportunities to take a role in disaster and mitigation education. Educational media for disaster mitigation that has been used to provide understanding to the community has been widely disseminated. It is necessary to explore the formal aesthetics of educational content design on disaster mitigation as a disaster education effort through various possibilities in communication approach through vernacular visual language in disaster education. The research method use ethnography with qualitative descriptive analysis. The results of the research will be used as recommendation to the stakeholders and designers as design guideline that consider the site specific factor of each disaster characteristic.